A rural-urban comparison of client-provider interactions in patent medicine shops in South West, Nigeria. (2012)
The increasing prominence of patent medicine vendors (PMVs) in healthcare provision makes information about how they operate of interest. This study assessed consumers' behavior and PMVs' performance in the treatment of childhood illnesses in rural and urban communities in South West Nigeria. Non-participatory observations were carried out in 163 licensed patent medicine stores in Oyo State, Nigeria. Many PMV shops (70.6% rural and 6l.9% urban; p = 0.141); stocked non proprietary drugs. Clients often requested for drugs by name (75.4% urban versus 62.2% rural; p = 0.002) and PMVs mostly sold drugs as requested without questions (65.3% urban 57.8% rural; p = 0.07). Inappropriate treatment practices and invasive procedures were observed more often in urban PMVs shops (p < 0.001). PMVs functioned mostly as sales persons supplying clients' drug requests. Strategies to improve PMV treatment practices should include caregiver education to be effective.